(untitled) (Italian Journal of Public Health, 2008)
Tropospheric ozone (O3) and Particulate Matter (PM) have become a major concern in most European cities. In particular, in Italy the O3 concentrations exceed the limits established for the protection of both human health and vegetation. More integrative studies are revealing that urban trees could concretely help in improving air quality, not only because of their well known aesthetic and recreational benefit, but also for their capability to reduce air temperature and to remove air pollutants. This reduction takes place both directly, by dry deposition to plant surfaces and uptake through stomata, and indirectly, by mitigation of the urban heat island intensity by canopy transpiration and building shading, that lowers the activity of chemical reactions that led to the formation of photochemical pollutants in air. This is of particular importance especially for those cities located in the Mediterranean Basin, whose urban vegetation is often characterized by VOC-emitting species that can contribute significantly to the O3 formation and destruction dynamics. The aim of this paper is to present a short review of ecological research performed on vegetation of the metropolitan area of Rome, at different spatial and temporal scale, in order to evaluate the functional role of urban green to monitor and improve urban air quality. In the frame of the project HEREPLUS (EU FP7), all of this information, opportunely integrated with climatic and pollutant data, will be implemented in a GIS and, by the use of geo-statistical methods, the ameliorating effect of urban vegetation will be quantified and mapped.